1972
DOI: 10.1136/bmj.4.5842.697
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Midday Meals of Senior Schoolchildren

Abstract: SummaryA survey of 565 senior schoolchildren showed that 41% took the school meal. It provided 27% of the daily recommended energy intake and 35% of the daily protein intake set by the Department of Health and Social Security. Of the children who did not take the school meal 4% had a meal which compared favourably with it, though an equal number ate no lunch at all. The remainder either brought snacks from home or bought foods which were found to be both low in protein, iron, and calcium, and high in sugar. Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Kent secondary schoolchildren had a higher uptake of school meals (80%) than London secondary schoolchildren (41 %) (Richardson and Lawson, 1972). More Kent secondary schoolchildren (16 %) had lunch at home than in the London survey (4%).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Kent secondary schoolchildren had a higher uptake of school meals (80%) than London secondary schoolchildren (41 %) (Richardson and Lawson, 1972). More Kent secondary schoolchildren (16 %) had lunch at home than in the London survey (4%).…”
Section: Discussionmentioning
confidence: 86%
“…In two recent studies school meals did not reach the standard set by the Department of Education and Science (Bender, Magee, and Nash, 1972;Richardson and Lawson, 1972). A study of child health and nutrition in Sweden found school lunches provided lower energy intake and were higher in fat content than the recommended Swedish dietary allowances for school lunches (Samuelson, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…A 1906 and subsequent legislation, provision of school lunches became a requirement for all number of studies have examined the contribution of school lunches but few have state schools and until the 1980 Education Act, specific standards governed their nutritional included work on packed lunches-a potential omission since only 50% of pupils take school content, although these were not always met (Nelson & Paul, 1983;Richardson and Lawson, lunches (Gardner Merchant, 1991;White et al, 1992). A notable exception is Nelson & Paul 1972;Bender et al, 1972;McAllister et al, 1981). Concern about the possible effects of (1983).…”
Section: Introductionmentioning
confidence: 99%